Cover Image. Issue 11 (4th October 2021) - Salvetti, Alessandra; Degl'Innocenti, Andrea; Gambino, Gaetana; van Loon, Jack J.W.A.; Ippolito, Chiara; Ghelardoni, Sandra; Ghigo, Eric; Leoncino, Luca; Prato, Mirko; Rossi, Leonardo; Ciofani, Gianni
Abstract : The cover image is based on the Research Article Artificially altered gravity elicits cell homeostasis unbalance in planarian worms, and cerium oxide nanoparticles counteract this effect by Gianni Ciofani et al., https://doi.org/10.1002/jbm.a.37215 .